2020
DOI: 10.3390/s20082398
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sheet Resistance of Inkjet-Printed Ag-Layers on Flexible, Uncoated Paper Substrates Using Van-der-Pauw’s Method

Abstract: With the growing significance of printed sensors on the electronics market, new demands on quality and reproducibility have arisen. While most printing processes on standard substrates (e.g., Polyethylene terephthalate (PET)) are well-defined, the printing on substrates with rather porous, fibrous and rough surfaces (e.g., uncoated paper) contains new challenges. Especially in the case of inkjet-printing and other deposition techniques that require low-viscous nanoparticle inks the solvents and deposition mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Similar results were obtained for a wavelength of 385 nm, even though the resistivity exhibited larger values in all samples, suggesting the shorter wavelength of UV-LED are more effective for better electrical performance. The minimum resistivity of 5.44 × 10 −6 Ω•cm (sheet resistance of 72.6 mΩ/sq), comparable value from Ag films photo-sintered with IPL [55], was obtained from the optimum photo-sintering conditions (300 mW/cm 2 and 50 min). Comparing to values of thermally sintered silver film (Figure 5), the films irradiated with the UV-LED modules appeared to have better electrical conduction, regardless of the wavelength.…”
Section: Resultssupporting
confidence: 60%
“…Similar results were obtained for a wavelength of 385 nm, even though the resistivity exhibited larger values in all samples, suggesting the shorter wavelength of UV-LED are more effective for better electrical performance. The minimum resistivity of 5.44 × 10 −6 Ω•cm (sheet resistance of 72.6 mΩ/sq), comparable value from Ag films photo-sintered with IPL [55], was obtained from the optimum photo-sintering conditions (300 mW/cm 2 and 50 min). Comparing to values of thermally sintered silver film (Figure 5), the films irradiated with the UV-LED modules appeared to have better electrical conduction, regardless of the wavelength.…”
Section: Resultssupporting
confidence: 60%
“…1, 2 and 3L of the Ag and Au conductive inks were printed in Van der Pauw structures of 4×4 mm 2 over the several proposed substrates. [ 73 ] These structures were printed on the four paper substrates at the same resolution (DS 15 µm for Au ink, and 20 µm for Ag ink), the patterns were dried 15 min at 80 °C and sintered 1 h at 140 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The latter monitors the air flow across the substrate, and it could be related to its porosity and absorption behavior [ 30 ]. In general, it is desired to use non-porous over porous substrates to prevent excessive absorption of the functional ink and to achieve homogenous conductive layers on top of the substrate [ 29 , 32 ]. On the other hand, a minimum amount of ink penetration is required for adhesion, and thus stability and durability of the silver prints.…”
Section: Resultsmentioning
confidence: 99%
“…Although fiber-based substrates are widely used in the conventional printing industry, the field of printed electronics on paper or cardboard substrates is rather limited [ 29 , 31 ]. The observed challenges towards printability and electrical performance are related to the surface roughness, absorption capacity, barrier properties, thermal stability and surface energy of fiber-based substrates [ 29 , 32 , 33 ]. Despite these hurdles, Xie et al have shown that ordinary low-cost paper is suitable for inkjet printed smart packaging applications with optimized properties of conductivity [ 34 ] and Pereira et al have demonstrated the potential of screen printing on paper substrates to develop NFC tags [ 35 ].…”
Section: Introductionmentioning
confidence: 99%